FSKTM Presentation Management System for Postgraduate Study using Web Application (PHP) - Chu, Zhen Hau; Hairulnizam Mahdin, (Applied Information Technology And Computer Science, 2021)
The current system for arranging postgraduate presentation schedule is using Microsoft Excel. This method is lack of efficiency in terms of information displacement and recording purpose. The recording is using file system that is not online and only reside in one computer. Therefore, this project aims to develop a web-based postgraduate presentation management system that can store data and retrieve data from online database. This way will change the data repository from computer local disk to online database. Therefore, data can be retrieved from online database. This system also provides many error-checking prevent error like assigning supervisor as panel or both panels are the same panel. The software development methodology used in this project is agile model which is an iterative model. It helps developer to deliver a better-quality system that meet to user requirement after every iteration. Data flow diagram, entity relationship diagram, flowchart and user interface are made before coding phase to show the system design.